Welcome the "new kid on the block" into the family: artificial intelligence in oral and maxillofacial surgery. Issue 1 (January 2020) - Pereira, Karishma Rosann; Sinha, Ramen
Abstract: Recent decades have witnessed the genesis and progressive application of intelligent machines and computer programs that have the ability to process information and execute cognitive functions similar to those of human logic and reasoning such as problem solving and decision making. That is artificial intelligence (AI) in a nutshell as envisioned by John McCarthy, "the father of AI". Healthcare has welcomed AI, giving rise to collaborations such as the Moorfields Eye Hospital and Google's DeepMind division in the screening and predicting of retinal disease. The use of AI by the maxillofacial surgical fraternity is, however, limited. We wish to highlight the fact that surgeons are uniquely positioned to help drive these innovations rather than passively waiting for the technology to become useful.